Breast Cancer-Therapeutic Challenges, Research Strategies and Novel Diagnostics - Nabieva, Naiba (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Thanks to the breast cancer research of recent decades, effective methods and strategies have been established, allowing the mortality rates of breast cancer patients to decrease more and more. However, we still face many challenges. The role of certain biomarkers or mutations is still not clear for treatment and surveillance. Novel drugs are often associated with a different spectrum of adverse events than that seen for conventional therapies, accordingly having an impact on patients' compliance behaviors. In breast cancer surgery, in some cases, the question remains whether to escalate or deescalate. Additionally, with regard to diagnostics, in a digitalized world, home-based tools and therapy monitoring options are of high importance, especially under the tough conditions and supply problems seen during the COVID-19 pandemic.This Special Issue gathers original research articles and reviews demonstrating therapeutic challenges, current research strategies, and novel diagnostics in breast cancer.